Keywords VOS - Panneerselvam, Senthilkumar (SciLifeLab Serve, 2026)
Co-occurrence plots created using VOS viewer . There are three plots in total, each based on publications from a different SciLifeLab reporting group (i.e. affiliated researchers, infrastructure units, and SciLifeLab fellows). In each plot, we have considered the KeyWords Plus associated with each paper.